Dermatology: how to manage acne in skin of colour - Claire Chiang; Madison Ward; Melinda Gooderham (BioExcel Publishing Ltd, 2022)
Acne vulgaris is a prevalent dermatological condition worldwide but is especially challenging to treat in individuals with skin of colour (SOC). Corresponding to Fitzpatrick skin phototypes III-VI, people of African, Asian, Middle Eastern and Hispanic ethnicity are considered to have SOC. With the additional risk of postinflammatory hyperpigmentation (PIH) as a consequence of inflammatory acne or its respective treatment, managing acne in this population holds significant importance. PIH adversely impacts self-esteem and quality of life and, thus, is usually the patient's priority of treatment. Available acne treatments are similar for all skin types. However, some are more beneficial for individuals with SOC, in particular by targeting both active acne lesions and PIH. The acne treatment literature was searched for topical and systemic treatments that were specifically studied in the SOC population. These treatments included topical agents, such as retinoids and azelaic acid, in addition to topical antibiotics and benzoyl peroxide. Newer formulations and combined regimens reported effective in reducing lesions are less likely to induce PIH and may treat pre-existing PIH. Moisturiser use, titrating doses and patient education are strategies to minimize irritation and improve adherence. In addition, systemic therapies, including oral antibiotics, isotretinoin, oral contraceptives and spironolactone, are efficacious for refractory acne or more severe cases but specific studies in SOC are lacking. Chemical peels may improve acne and target PIH directly. Overall, based on limited evidence, topical and systemic therapies are well tolerated in the SOC population but efficacy should be balanced with the risk of adverse effects. This narrative review aims to highlight formulations and combination therapies that are effective and safe for treating acne and PIH in patients with SOC.